Subcrhonic Toxicity of Curcuma longa (Tumeric) Rhizoma Extract on Rats - Yani Mulyani; Patonah Hasimun; Siti Nurjanah (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Toxicity is a condition that indicates a harmful effect contained in a substance such as turmeric, which is an effective traditional medicinal plant used for antihypertensive treatment. Therefore, this study aims to determine the effect of repeated dosing of turmeric (Curcuma longa L.) rhizome extract. This subchronic toxicity study was divided into 4 groups, namely 1 normal treated with 0.5% Na-CMC, and 3 treatments with turmeric extract at doses of 50, 100, and 200 mg/kg BW for 28 days with each group consisting of 5 males and 5 female Wistar rats. The results showed that the turmeric extract at doses of 50, 100, and 200 mg/kg BW did not cause toxicity to liver and kidney biochemistry nor contain any toxic substances that might cause anemia or other abnormalities. Furthermore, histopathological examination showed that the tissues were normal. This indicates that the turmeric rhizome extract at all dose variations indicate non-toxic when used in traditional medicine.